2014
DOI: 10.1209/0295-5075/105/37002
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer study of magnetic fluctuation in the iron-arsenic layer of Sr 2 VO 3 FeAs

Abstract: Mössbauer spectra of the freshly prepared Sr2VO3FeAs compound have been measured under different temperatures. We observed a variation of the spectral shape with decreasing temperature. The obvious diminution of quadrupole splitting occurred at about 63 K is ascribed to the weak influence of the ferromagnetic transition of the V-O layer to the spatial distribution of Fe-3d electrons, whereas the influence of the antiferromagnetic transition in the V-O layer is negligible. Below the superconducting transition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…6 (a) and (b). The IS values of the 4d and 8h sites at 294 K are 0.225(2) mm/s and 0.227(1) mm/s, respectively, which are slightly larger than the typical values for iron-silicon compounds in which Fe carries no moment [25,26], but are about 0.2 mm/s smaller than that in the iron-pnictide compounds [10][11][12]. The temperature dependencies of the IS corresponding to the two sites are very similar, and no anomalies can be observed around T c (Fig.…”
Section: A Structure and Superconductivitymentioning
confidence: 70%
See 2 more Smart Citations
“…6 (a) and (b). The IS values of the 4d and 8h sites at 294 K are 0.225(2) mm/s and 0.227(1) mm/s, respectively, which are slightly larger than the typical values for iron-silicon compounds in which Fe carries no moment [25,26], but are about 0.2 mm/s smaller than that in the iron-pnictide compounds [10][11][12]. The temperature dependencies of the IS corresponding to the two sites are very similar, and no anomalies can be observed around T c (Fig.…”
Section: A Structure and Superconductivitymentioning
confidence: 70%
“…Due to the absence of commonly available Mössbauer nuclides in the cuprates, most studies were accomplished either by partial substitution of copper atoms by 57 Fe and/or 119 Sn, or by using resonant isotopes of the rare earth metals, like 151 Eu, which increases the degree of difficulty of the measurements and reduces the clarity of the results [3,5,8,9]. Recently, the discovery of iron-based superconductors, that naturally contain the common Mössbauer nuclide, 57 Fe, has triggered intense Mössbauer studies of these superconductors [10][11][12][13][14][15]. Superconductivity in iron-pnictides is usually achieved by doping a magnetic parent compound with electrons or holes, or by application of chemical or physical pressure, and thereby, suppressing the magnetic order, suggesting that superconductivity and magnetism are closely related in this system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a third route towards SC, namely the self doping effect, was realized in Sr 2 VFeAsO 3 11 , Ba 2 Ti 2 Fe 2 As 4 O and RbGd 2 Fe 4 As 4 O 2 2,5,12 . Rich magnetism has been found and studied with SC for Sr 2 VFeAsO 3 and it is found that magnetism and SC coexist in the freshly prepared Sr 2 VFeAsO 3 13 . However, the magnetism disappeared after long term storage of the sample indicating that it is meta-stable in nature which might be induced by defects or residual stress .…”
Section: Introductionmentioning
confidence: 99%
“…Superconductivity in iron-pnictides is usually achieved by doping a magnetic parent compound with electrons or holes, or by application of chemical or physical pressure, and thereby, suppressing the magnetic order, suggesting that superconductivity and magnetism are closely related in this system. Although there are some studies on iron-based superconductors, which state that Mössbauer spectral parameters show anomalies near T c , in these materials it is hard to attribute the variation of the hyperfine parameters observed by Mössbauer spectroscopy to purely magnetic or purely superconducting origins [12,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%